“Lo invisible cotidiano”. El trabajo doméstico y su representación en la novela gráfica española - Potok, Magda (Studia Romanica Posnaniensia, 2024)
In recent years, there has been a growing interest in graphic narratives that explore family histories, particularly focusing on women and their roles in daily life. Works such as El ala rota by Antonio Altarriba y Kim (2016), Estamos todas bien by Ana Penyas (2017) and Regreso al Edén by Paco Roca (2020) delve into the lives of mothers and grandmothers, aiming to reclaim their memories and acknowledge the significance of domestic and care labor, often overlooked in Spanish history. The graphic novels offer a dual representation, combining text and images to depict the struggles women faced in different historical periods and the inequalities embedded in domestic work. We aim to critically examine this societal change through literature, which blends history, sociology, and personal experience.